2016
DOI: 10.17159/2310-3833/2016/v46n2a9
|View full text |Cite
|
Sign up to set email alerts
|

In-hand manipulation (IHM) in children 6 and 7 years of age: A follow-up study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…When participants did consult primary literature, this included familiar sources such as the guideline for Screening Hand Skills described in the Occupational Therapy for Children textbook. Furthermore, their familiarity with the UFS IHM-C, which was published in the South African Journal of Occupational Therapy (SAJOT) 13,25 attested to participants accessing research published locally.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When participants did consult primary literature, this included familiar sources such as the guideline for Screening Hand Skills described in the Occupational Therapy for Children textbook. Furthermore, their familiarity with the UFS IHM-C, which was published in the South African Journal of Occupational Therapy (SAJOT) 13,25 attested to participants accessing research published locally.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants (n=242; 82.9%) indicated that they were not familiar with any of the listed formal assessment methods. Of the remaining 50 (17.1%) that indicated their familiarity 28 , (9.6%), indicated that the Screening Activities of Hand Skills guideline described by Exner in the Occupational Therapy for Children 6th Edition textbook was the most familiar to participants, followed by an additional fine motor assessment, the FDT for children (n=17; 5.8%), and the in-hand manipulation assessment, UFS IHM-C, developed in South Africa by Visser et al 13,25 (n=15, 5.1%). However, for all the instruments, there were fewer responses of their reported use in comparison to the familiarity indicated.…”
Section: Formal Assessment Methodsmentioning
confidence: 99%
See 3 more Smart Citations